Contract farming of pineapple the case of cooperative members in Polomolok, South Cotabato - Nagar, Cherry May M.
Contract farming is adopted, on majority, by food processing companies in Mindanao area. The growing trend of pineapple contract farming in the area is brought about by the increasing demand for the commodity worldwide. The scheme is adopted to make pineapple production cost-effective and efficient. This study aimed to analyze the characteristics of the existing contract growing scheme of pineapple in Polomolok, South Cotabato. Reason(s) that encourage farmers to join contract farming are likewise discussed as well as its effect(s) to the economic living condition to the farmers.Contract Farming framework of Eaton and Shepherd (2001) was adopted in the study to aid the proponent in understanding the venture. Primary data was gathered through direct interview/surveys to purposely selected farmers and key players of the cooperatives. The study found out the pineapple contract farming is played by three major actors; sponsor, company X; farmers, cooperatives members; and government institutions, namely: Land Bank of the Philippines (LBP), Department of Agrarian Reform (DAR), and Cooperative Development Authority (CDA). Farmers' main reason for joining contract farming is the existence of financial assistance provided by LBP. It was also ascertained that contract farming had improved the living condition of some farmers, while others became worst.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines Mindanao
Keywords: Pineapple farmers -- Polomolok, South Cotabato(Philippines) -- Agriculture cooperatives